Associated Factors for the Development of Alcohol Withdrawal Delirium - Chien, Nguyen Huu; Thi Thuy An, Le; Viet Chung, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 38 No 3, 2022)
Abstract: This study was conducted to evaluate some associated factors predicting the development of alcohol withdrawal delirium; 56 patients in E hospital were divided into two groups including group 1 of 28 patients diagnosing mental and behavioral disorders due to use of alcohol, withdrawal state with delirium (F10.4) and group 2 of 28 patients diagnosing mental and behavioral disorders due to use of alcohol, withdrawal state (F10.3) according to ICD-10 criteria; Method: cross-sectional study; Result showed that clinical features are sweating and seizure; laboratory tests are GGT, total bilirubin, direct bilirubin, platelet emerged as associated factors of alcohol withdrawal delirium. The level of direct bilirubin over 13 μmol/L is the strongest associated factor with OR(95%CI) 6(1.648-21.840). These risk factors about alcohol dependence featured can be easily evaluated in a clinical setting for physicians to identify patients at risk for developing alcohol withdrawal delirium to make intensive therapy plans for them. Keywords: Alcohol withdrawal delirium, risk factor, clinical feature, laboratory test.